Peran Badan Usaha Milik Desa Makmur Mulia Dalam Pemberdayaan Ekonomi Lokal - Ramdhani, Kurnia; Hakim, Imamul; Amalia, Rahmi (Journal of Islamic Economics Development and Innovation (JIEDI), 2022)
Badan Usaha Milik Desa (BUMDes) is a business entity formed by the village government which is one of the government programs that aims to improve the welfare of rural communities and to build and develop the potential of the village. BUMDes capital comes from the village's original income and is expected to be useful for the village community. This study aims to determine the role of BUMDes in local economic empowerment in Sukamulia Timur Village, Lombok Timur Regency, Nusa Tenggara Barat Province. The research method used in this study is a qualitative descriptive method to describe case studies. Data collection techniques using interviews, and documentation related to research. The data analysis technique in this study was carried out qualitatively. The results of this study showed that local economic empowerment in the village of Sukamulia Timur through BUMDes has been going quite well, this is shown by the sale of animal feed managed by BUMDes can make it easier for the people of Sukamulia Timur Village who have livestock to look for feed, besides that, it is facilitated by the credit payment system. for the feed purchased and the price is relatively cheaper compared to prices in other stores.